Evaluating the Effect of the Ketogenic Diet on the Reproductive and Metabolic Parameters in Iraqi Females with Polycystic Ovary Syndrome - Sattar Harbi, Nazar; Hussein J. AL-Qaisi, Alaa; Hairunisa, Nany (Al-Nahrain Journal of Science, 2025)
Polycystic ovarian syndrome is the prevailing endocrine condition among females in their reproductive age. Clinically, it is characterized by irregular or delayed ovulation, excessive androgen levels, and the appearance of polycystic in ovaries. It is linked to a greater incidence of metabolic syndrome. Although it is related to various hereditary and environmental factors, insulin resistance is an essential factor in its development. The objective of our conducted research was to observe the impacts of the ketogenic diet on the reproductive and metabolic indicators in females who have been diagnosed with polycystic ovary syndrome. Eighty females of reproductive age have participated in the current investigation. During three months of adhering to the ketogenic diet, high statistical reductions (P=